Belia dan program kesukarelawan di Malaysia: Satu kajian empirikal (youth and volunteerism in Malaysia: An empirical study) - Syed Hussain, Tuan Pah Rokiah; Yasin, Lilah (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Youth appreciation of volunteerism needs to be given attention if only because voluntary activities carried out without genuine appreciation of the volunteerism spirit does not really benefit the participants. This study evaluated the level of Malaysian youth appreciation of the spirit of volunteerism with respect to six appreciation constructs, namely, understanding, emotion, belief, practices, attitudes and motivation The study was conducted throughout the states in Peninsular Malaysia involving 500 randomly sampled youth aged between 15 and 30 and comprising all ethnic groups. Results of the statistical analysis showed that the level of Malaysian youth appreciation of the spirit of volunteerism was satisfactory except for the two parameters of emotion and motivation.In the case of emotion the study indicated the youth relative reluctance when volunteer programmes were located in areas suffering from diseases, unhygienic conditions and lacking in public amenities as in disaster areas.Yet, it was in such a situation that the keen spirit of volunteerism was most needed.This thus points to the imperative of improving the motivational side of youth volunteerism programmes in the country.